Rapid Screening of Acetylcholinesterase Inhibitors by Effect-Directed Analysis Using LC × LC Fractionation, a High Throughput in Vitro Assay, and Parallel Identification by Time of Flight Mass Spectrometry - Ouyang, Xiyu; Leonards, Pim E G; Tousova, Zuzana; Slobodnik, Jaroslav; de Boer, Jacob; Lamoree, Marja H (Analytical chemistry, 2016)
Effect-directed analysis (EDA) is a useful tool to identify bioactive compounds in complex samples. However, identification in EDA is usually challenging, mainly due to limited separation power of the liquid chromatography based fractionation. In this study, comprehensive two-dimensional liquid chromatography (LC × LC) based microfractionation combined with parallel high resolution time of flight (HR-ToF) mass spectrometric detection and a high throughput acetylcholinesterase (AChE) assay was developed. The LC × LC fractionation method was validated using analytical standards and a C18 and pentafluorophenyl (PFP) stationary phase combination was selected for the two-dimensional separation and fractionation in four 96-well plates. The method was successfully applied to identify AChE inhibitors in a wastewater treatment plant (WWTP) effluent. Good orthogonality (>0.9) separation was achieved and three AChE inhibitors (tiapride, amisulpride, and lamotrigine), used as antipsychotic medicines, were identified and confirmed by two-dimensional retention alignment as well as their AChE inhibition activity.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; Time Factors; časové faktory; Acetylcholinesterase; lidé; Chromatography, High Pressure Liquid; cholinesterasové inhibitory; Cholinesterase Inhibitors; High-Throughput Screening Assays; acetylcholinesterasa; rychlé screeningové testy; Humans